Inflamação sistêmica e estado nutricional associados às doenças crônicas bucais em adolescentes - CARMO, Cadidja Dayane Sousa do (2016)
Objective: Chronic oral diseases are consistently associated with chronic non-communicable diseases in adults and, considering that little is known about the underlying mechanisms that link these alterations, the present study had as objectives: 1- Analyze the effects of the " Systemic inflammatory load "on the extent of periodontal diseases in adolescents (Chapter 1); 2 - To estimate the association between intake of added sugars, obesity and the correlation of levels of interleukin 6 (IL-6) in the latent variable "burden of chronic oral diseases" in adolescents, through the modeling of structural equations (Chapter 2). Methods: A crosssectional observational study was carried out in São Luís, Maranhão, Brazil, from January 2014 to July 2016. With a complex random sample of students enrolled in São Luís state public network, it was applied in three stages: 1st stage- school; 2nd stage - class and 3rd stage - student. The sample consisted of 405 adolescents aged 17 and 18 years. Data were collected using a sociodemographic questionnaire, nutritional assessment (anthropometry and diet evaluation), blood tests, reading of serum inflammatory markers, blood pressure measurement and odontological examination. The data were analyzed by structural equations modeling, with the construction of latent variables based on the convergent factor loads that formed each latent variable in an exploratory factorial analysis (AFE). Later, they were validated by means of confirmatory factorial analysis (AFC), using software Mplus version 7.0. Results: Adolescents with greater extension of periodontal diseases presented higher systemic inflammatory load (CP = 0.267, p = 0.005) and lower socioeconomic status (CP = - 0.283, p = 0.018). Adolescents with higher body mass index presented higher inflammatory load (CP = 0.224, p = 0.001) and higher levels of diastolic blood pressure (CP = 0.143, p = 0.003) (Chapter 1). Adolescents with chronic oral diseases had higher intake of added sugars (CP = 0.252, p = 0.017), higher values for serum levels of interleukin-6 (CP = 0.137, p = 0.024) and lower socioeconomic conditions (CP = 0.462, P = 0.004). The results also indicated that adolescents with higher values of body mass index had higher serum levels of interleukin-6 (CP = 0.220, p = 0.002). Conclusion: The construction of the latent variables allowed the observation of the proposed relationships in the theoretical models of the present study. The good constructs formed were able to demonstrate some expected associations, considering also the possibility of reduction of the measurement error in the definition of the variables and the lower probability of type II error (false negative), due to the modeling analysis of structural equations performed in the Present study. It has been shown that the higher systemic inflammatory load already present in adolescents with greater extension of periodontal diseases and that chronic oral diseases may have a common risk factor among them, the inadequate consumption of addition sugars. Higher levels of IL-6 were associated with obesity and also correlated with the higher "load of chronic oral diseases", suggesting the presence of chronic inflammation of low intensity is underlying the associations shown here.